Frecuencia y factores de riesgo asociados a desnutrición en niños de 1 a 5 años de edad del barrio Menfis Central - Romero Armijos, Jennifer Deyanira (2023)
Child malnutrition represents a significant public health issue in Ecuador, with consequences for the affected children and society. As it is an issue of relevance, this descriptive, crosssectional, observational, mixed approach, whose purpose was to update on the frequency and risk factors associated with malnutrition in children aged 1 to 5 years in the Menfis Central neighborhood. Through door-to-door visits, a random sample of 50 children meeting the inclusion criteria was obtained; of those anthropometric data were recorded and nutritional status was classified; the parents of 22 children who were found to be malnourished were administered a targeted survey to identify risk factors associated with malnutrition. The collected information was organized using Microsoft Excel 2016 with what was observed that malnutrition corresponds to 44% of the children, with 54.54% (n=12) being boys and 45.45% (n=10) girls. Acute malnutrition was present in 18.18% (n=4) of the sample, while chronic malnutrition was found in 81.81% (n=18). The most common risk factors associated with malnutrition in children in the Menfis Central neighborhood, in order of frequency, were a monthly income less than the basic salary at 72.72% (n=16), educational level of the tutors: primary level 27.27% (n= 6), secondary 59.09% (n=13), insufficient prenatal check-ups at 27.27% (n=6), incomplete anthropometry at birth and gestational age at 13.63% (n=3), and duration of breastfeeding and introduction of complementary feeding at 9.09% (n=2). It is concluded that in this study, malnutrition prevailed in males, and chronic malnutrition was more prevalent than acute malnutrition